Assessing adolescent immunization options for pertussis in Canada: A cost-utility analysis. Issue 7 (11th February 2020) - Anyiwe, Kika; Richardson, Marina; Brophy, Jason; Sander, Beate
Abstract: Background: Adolescent tetanus, diphtheria and pertussis (Tdap) immunization helps prevent pertussis infection. Timing of Tdap receipt represents an important facet of successful adolescent pertussis immunization. Potential strategies for timing of vaccine administration are each associated with different benefits – including disease prevention – and costs. The objective of this study was to assess the cost-utility of adolescent pertussis immunization strategies in Canada. Methods: A cost-utility analysis was conducted using a pertussis disease history-simulating Markov model, with adolescents (beginning at age 10 years) as the cohort of interest. The model assessed three Tdap vaccination strategies: (1) immunization of 10 year olds, (2) removal of adolescent vaccination, and (3) immunization of 14 year olds (status quo). The analysis was conducted from a healthcare payer perspective and used a lifetime time horizon. Primary outcomes included life years, quality-adjusted life years (QALYs), health system costs, and an incremental cost-effectiveness ratio (ICER). Costs and outcomes were discounted at 1.5 percent annually. Deterministic and probabilistic sensitivity analyses were performed to assess parameter uncertainty. Results: The current recommended adolescent immunization strategy (at age 14) resulted in an average of 40.4432 expected QALYs and 26.28 per individual. This strategy was dominated by immunization at 10 years and no immunization. Compared to no immunization, immunizing adolescents at age 10 had an ICER of 74, 899 per QALY. Results were most sensitive to the incidence of pertussis and the utility of moderate or severe pertussis. At a cost-effectiveness threshold of 50, 000/QALY, removal of adolescent vaccination represented the most cost-effective strategy in 78% of simulations. Conclusion: Analysis assumes a policy context where immunization of pregnant women is recommended. Findings suggest that alternate adolescent Tdap vaccine strategies – either immunization of 10 year olds, or removal of the adolescent vaccine – are more cost-effective than the current practice of immunizing 14 year olds.